The mental skills included in the mathematics book for the second intermediate grade in the light of the Marzano model (Journal of the College of Basic Education, 2022)
This current university research presents the educational inclusion in the content of the mathematics book for the second intermediate grade within the Marzano model in the Republic of Iraq for the year 2021) / 2022 AD.By answering the research question:The first question:What is the percentage of including mental skills in the mathematics book for the second intermediate grade?The researcher adopted the descriptive-analytical approach, in order to suit the goal of the research, as the current research sample consisted of the scientific material in the mathematics textbook for the second intermediate grade, and the idea unit was adoptedWhich may be explicit or implicit as a unit for recording and repetition as a unit for counting, and to achieve the goal of the research, the researcher prepared an initial list of (main and sub mental skills) after reviewing the literature and studies that dealt with analyzing the content of textbooks according to mental skills.Then this list was presented in its initial form to a number of arbitrators with expertise and competence, where the list obtained agreement on more than (93%) of the arbitrators' opinions.The content of the mathematics book for the second intermediate grade was analyzed according to the main and sub mental skills. A sample of the analysis sample was presented to a number of arbitrators with expertise and competence and they agreed on the validity of the analysis process, and the confirmation of the stability of the analysis process came in two ways: the first is the researcher with himself and the second is the researcher with another analyst after a specified period of time (four weeks) and I got The percentage of agreement ranged between (89% - 91%), as the data were processed and the reliability rates were used using the Holsti equation.The following results were obtained:The mathematics book for the second intermediate grade obtained the repetitions of mental skills, as it obtained 785) recurrences with a percentage of (100%).As for the main skills:Where the category of organization skills ranked first in all books after it obtained (319) recurrences, at a rate of (40.6%).It is followed by the category of analysis skills in the second place, after it got (110) recurrences and at a rate of (14%).Then came the rest of the categories in varying proportions.As for the sub-skills: The skill of arranging ranked first for the three books on (175) recurrences and at a rate of (22%).Then the acting skill ranked second after it collected (82) recurrences at a rate of (10%).The other sub-skills came in varying degrees of interest from the textbook, while the skills of formulating questions and the skill of identifying main ideas were neglected.In light of this, the researcher recommended the need for balance in the percentages of including mental skills in the mathematics book for the second intermediate grade, and came up with a number of recommendations and suggestions.